Nutrition Science Communication: "If It's Transparent, Is That Why We Cannot See It?". Issue 2 (March 2021) - Rowe, Sylvia; Alexander, Nick
Abstract : With the evolving complexities of nutrition and health science communication posing challenges to those tasked with translating and delivering information to the public, there are increasing calls for openness—both at the research and research-communication levels. It has been widely accepted that openness is a pathway to increasing public trust in emerging nutrition and other health science. Yet, about one of the key components of openness, transparency, there has been relatively little detailed discussion in the literature; the concept of transparency in the communication of science has been especially opaque. In the present article, the authors explore what transparency might mean in the context of communication and what pitfalls or positive outcomes it may offer to public understanding of nutrition and other health science. They propose strategies for managing and enhancing the delivery of transparent information in a modern communication landscape full of landmines, with its foreshortened news cycles, multiplicity of sources, and social media outlets of varying reliability.